PPy‐encapsulated SnS2 Nanosheets Stabilized by Defects on a TiO2 Support as a Durable Anode Material for Lithium‐Ion Batteries - Wu, Ling; Zheng, Jie; Wang, Liang; Xiong, Xunhui; Shao, Yanyan; Wang, Gang; Wang, Jeng‐Han; Zhong, Shengkui; Wu, Minghong (Angewandte Chemie International Edition, 2019)
Nanostructured‐alloy‐type anodes have received great interest for high‐performance lithium‐ion batteries (LIBs). However, these anodes experience huge volume fluctuations during repeated lithiation/delithiation and are easily pulverized and subsequently form aggregates. Herein, an efficient method to stabilize alloy‐type anodes by creating defects on the surface of the metal oxide support is proposed. As a demonstration, PPy‐encapsulated SnS2 nanosheets supported on defect‐rich TiO2 nanotubes were produced and investigated as an anode material for LIBs. Both experimental results and theoretical calculations demonstrate that defect‐rich TiO2 provides more chemical adhesions to SnS2 and discharge products, compared to defect‐poor TiO2, and then effectively stabilizes the electrode structure. As a result, the composite exhibits an unprecedented cycle stability. This work paves the way to designing durable and active nanostructured‐alloy‐type anodes on oxide supports. PPy‐encapsulated SnS2 nanosheets strongly anchored onto a hydrogen‐treated TiO2 (H–TiO2) support have been successfully prepared as an anode for LIBs. As demonstrated by first principles, theoretical calculations, and experimental results, the superior binding between SnS2 and the H–TiO2 support via abundant Ti–S bonding, which is reinforced by the oxygen vacancy, contributes to the unprecedented cycle stability.